Masovia in prediction of Primate Stefan Wyszyński - Graczyk, Waldemar (Studia Theologica Varsaviensia, 2019)
Primate of Poland, Cardinal Stefan Wyszyński, in his teaching paid special attention to such notions as Church and Homeland. He focused on the value of the event, which was the Baptism of Poland in 966. Masovia was one of the stops on which the Nation’s faith was awakened, as well as the awareness of free and responsible man, creating history based on law and morality of the Decalogue. Primate was visiting Płock many times, during different occasions. He was preaching a word, which like the biblical grain was supposed to fall on the soil of human hearts and bring fruit. Historical and cultural role of Masovia, as a borough constituting an integral part of Polish state since its beginning and its contribution to culturalreligious development of Poland, was particularly emphasised during two Primate’s speeches: during millennial solemnities in 1966 and during the jubilee of a diocese in 1975. Primate Stefan Wyszyński, while talking about Masovia, emphasised its high position in building the State and the Church. Invoking figures, important for Masovia (bishops, priests, princes), he always pointed to the values, which they represented, and which were timeless. What Primate of Poland Cardinal Stefan Wyszyński said in Płock Masovia and about Masovia was fully reflected in the words of the Saint John Paul II uttered on 7 VI 1991 during his stay in Płock – “Płock has profoundly rooted in the history of Poland and the Church” – emphasising the role of this city, the capital of historical Masovia, in the millennial history of our Homeland.